WATER QUALİTY AS AN IMPORTANT FACTOR İN THE LİFE AND SUSTAİNABİLİTY OF MEDİCİNAL LEECHES - Cafer Bulut (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2026)
Water quality is a critical ecological factor that determines the survival, physiological performance, and sustainable utilisation of medicinal leeches. This study evaluated the effects of major physicochemical and microbiological water parameters on the health and viability of medicinal leech populations under controlled freshwater conditions. Water temperature (15–24°C), dissolved oxygen (6.5–9.2 mg L⁻¹), pH (6.8–7.8), electrical conductivity (180–420 µS cm⁻¹), and total dissolved solids (110–260 mg L⁻¹) were identified as the optimal environmental ranges supporting normal activity and reproduction. In contrast, dissolved oxygen levels below 4.5 mg L⁻¹ and ammonia concentrations exceeding 0.20 mg L⁻¹ resulted in a 32–41% reduction in feeding activity and a 24% decline in survival during the observation period. Elevated nitrate concentrations (>50 mg L⁻¹) and increased turbidity (>15 NTU) were associated with reduced cocoon production and delayed juvenile development. Microbiological analyses further demonstrated that excessive bacterial contamination significantly increased the risk of infection, decreasing reproductive success by approximately 28%. Multivariate statistical evaluation indicated that dissolved oxygen, ammonia, and pH collectively explained 78% of the observed variation in leech physiological performance and habitat suitability. Overall habitat quality exhibited a strong positive correlation with survival rate (r = 0.86, p < 0.001), emphasizing the ecological importance of maintaining stable freshwater conditions. The findings demonstrate that continuous monitoring of water quality parameters provides an effective approach for predicting habitat degradation and supporting conservation strategies for medicinal leeches. Protecting freshwater ecosystems from nutrient enrichment, chemical pollution, and microbial contamination is therefore essential not only for preserving natural populations but also for ensuring the sustainable production of medicinal leeches used in hirudotherapy and biomedical research. These results provide an ecological framework for developing evidence-based water quality standards and long-term conservation programs for medicinal leech resources.